Pelatihan Perawatan dan Penggunaan Mesin Pemotong Ubi untuk Meningkatkan Produktivitas UMKM Keripik Rumahan di Magelang - Her Tafga Arfanindita; Nur Hayati; M. Fendy Kussuma Hadi Sufyan; , Raka Mahendra Sulistiyo (Politeknik Piksi Ganesha Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) producing sweet potato chips in Mandiran Village, Salaman District, Magelang Regency face productivity challenges due to the manual slicing process. This method reduces production capacity, causes inconsistent slice thickness, and increases the risk of workplace accidents. Limited technical knowledge also prevents optimal use of existing slicing machines. This program aims to enhance operational capability through training on machine operation and maintenance, based on Standard Operating Procedures (SOP) and occupational safety principles. The method includes needs assessment, development of training modules, machine operation demonstrations, and evaluation of participants’ skills. The results indicate significant improvements in operational competence, work efficiency, and product consistency. The participatory approach also fosters a safer work culture and supports the sustainable adoption of appropriate technology, thereby strengthening the competitiveness of local food-based MSMEs.